GORODNYA – KIEV DEFENSIVE WALLS IN IX-XIII CENTURIES. PART TWO. THALLUS - Vadym Lukyanchenko (Місто: історія, культура, суспільство, 2017)
The article is a continuation of the author's research, which raises the question of the structural and functional features of the defence structures of the city of Kyiv in the IX-XIII centuries.